Ceilometer hourly average BLD estimates 2013-2015 - Hannah Marley (The University of Auckland, 2020)
This dataset contains valid hourly average boundary layer depth (BLD) estimates retrieved via ceilometer instrument. Times are in NZDT (New Zealand Daylight Time) and BLD estimates are in units of metres above ground level (magl). The criteria used to determine the validity of the BLD estimates is that outlined in Wagner & Schäfer (2017).
Keywords: Atmospheric sciences not elsewhere classified; Other environmental sciences not elsewhere classified